EVALUASI DAN SOSIALISASI POSTUR TUBUH DAN RISIKO TERJADINYA LOW BACK PAIN; PELATIHAN HOME BASED EXERCISE; SERTA PELAYANAN FISIOTERAPI PADA LANSIA - P.A.S. Saraswati; A. Wibawa; M.H.S. Nugraha; S.A.P. Thanaya (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Program Udayana Mengabdi was created with the aim of assisting the Indonesian government's program to improve the quality of life of the elderly through the management and prevention of low back pain, especially in Marga Dajan Puri Village, Tabanan Regency. Almost thirty percent of the elderly in the village had a history of low back pain (LBP) causing a decrease in activity affecting their quality of life. The elderly does not know that good posture was prevention to LBP. Home-Based Exercise (HBE) which is cheap and safe to do was also unknown to the elderly. The goals were achieved by carried out community service to educate good posture during activities and risk factors for LBP, and also physiotherapy health services. This program was implemented by 3 lecturers from the Physiotherapy study program and two students for two days. The forms of activities were evaluation and education of the elderly body posture and risk of LBP, HBE training and Physiotherapy services. Education will be delivered in simple language followed by the distribution of brochures on good posture, LBP prevention and HBE guidelines. Evaluation of understanding were done by asking and answering questions with the elderly. Keywords: LBP, elderly, posture, exercise, physiotherapy